LARANGAN EMAS DAN SUTERA UNTUK LAKI-LAKI: FAKTA DAN PENJELASAN DALAM HADIS - Mukhammad Alfani; Fauziyah, Farichatul (CV. Adiba Aisha Amira, 2024)
A phenomenon that has occurred recently is that many people do not care about laws or shari'ahs that are prohibited by religion. Especially when it comes to gold jewelry. Gold is a very valuable item, elegant and beautiful to wear. in a hadith that adheres to the religion of the use of gold and silk for men. This hadith describes the actions of the Prophet Muhammad SAW who firmly emphasized that these two materials (silk and gold) were haram for the men of his people. This hadith highlights that in Islam, there is a special prohibition on men wearing gold and silk. Scholars of four schools of thought agree that gold is used as jewelry such as necklaces, bracelets, rings, watches, etc. it is haram for men. This law applies both to a large and small extent. For women, it is legal to wear gold as jewelry. And gold itself also has bad or dangerous effects for men, including: It can cause disease which comes from the atoms in gold which can penetrate into the skin and into human blood, and if men wear gold in certain amounts and in long period of time.